Larvicidal activity and seasonal variation of Annona muricata (Annonaceae) extract on Plutella xylostella (Lepidoptera: Plutellidae) - PRÉDES-TRINDADE, ROSEANE CRISTINA; DE SOUZA-LUNA, JOSIANE; FERREIRA DE LIMA, MARIA RAQUEL; DA SILVA, PAULO PEDRO; GOULART-SANT’ANA, ANTÔNIO EUZÉBIO (Revista Colombiana de Entomología, 2011)
The diamondback moth Plutella xylostella is an important pest of cruciferous plants, particularly of cabbage (Brassica oleracea var. acephala). The activity of an ethanolic leaf extract of Annona muricata on the development of the larvae and pupae of a laboratory culture of P. xylostella was evaluated, together with the seasonal variation of this activity. Neonate larvae were fed with kale leaf discs that had been treated by immersion in solutions of A. muricata extracts, and the effects on the duration and viabilities of the larval and pupal phases of the insect were determined. The activities of the extracts varied significantly according to the time of collection of the leaf material and were maximal for leaves collected during the dry period of the year (October-February). At the highest concentration tested (5 mg.ml-1), the most active extract caused 100% larvae mortality; at lower concentrations, the duration of the larval phase was increased by up to 2.6 days and the larvae survival was significantly reduced. The pupal phase was affected far less by exposure to the extracts, although such duration was increased by up to 1 day in the presence of non-lethal  concentrations. The significance of these results with respect to the use of extracts of A. muricata for their insecticidal  activity is discussed.